1992
DOI: 10.1007/bf01989972
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of single-dose azithromycin versus doxycycline in the treatment of cervical infections caused byChlamydia trachomatis

Abstract: The efficacy of single-dose azithromycin therapy in the treatment of cervical Chlamydia trachomatis infections was compared to that of a standard seven-day course of treatment with doxycycline. Cervical samples from 60 patients reacted positively in an enzyme immunoassay for detection of Chlamydia trachomatis. In 31 patients Chlamydia trachomatis was isolated from the sample taken before treatment. Fourteen of the 31 patients were treated with doxycycline and 17 with azithromycin. All cultures of samples taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Only our results with minocycline appear to confirm this, which may be due to the fact that establishment of infection in the oviducts takes longer following intravaginal inoculation. A single dose of azithromycin was highly effective in preventing chlamydial shedding and therefore in preserving fertility, and this observation is in keeping with clinical experience in chlamydial cervicitis (17).…”
Section: Discussionsupporting
confidence: 80%
“…Only our results with minocycline appear to confirm this, which may be due to the fact that establishment of infection in the oviducts takes longer following intravaginal inoculation. A single dose of azithromycin was highly effective in preventing chlamydial shedding and therefore in preserving fertility, and this observation is in keeping with clinical experience in chlamydial cervicitis (17).…”
Section: Discussionsupporting
confidence: 80%
“…Both regimens have been shown to result in satisfactory cure rates in clinical trials (20,21,32,34,40,43,49).…”
Section: Infections Caused By the Obligate Intracellular Bacteriummentioning
confidence: 99%
“…TCs are the most effective of the antichlamydial agents (table 1) [4][5][6]. TCs inhibit protein synthesis of Chlamy dia by binding to the 30s subunit of ribosomes to block reorganization from RB to EB and multiplication of RBs.…”
Section: Tcsmentioning
confidence: 99%
“…In pregnant women, nursing mothers, or neonates, TCs are contraindicated and clarithromycin is recom mended. It has recently been reported that a single 1-g dose of oral azithromycin is as effective as standard regi mens of doxycycline, clarithromycin, or sparfloxacin in the treatment of genital chlamydial infections [6,10,11,17] , Effective single-dose therapy with azithromycin will reduce compliance problems.…”
Section: Treatments For Complicationsmentioning
confidence: 99%